Implementation difficulties of tutor support technologies in higher education - Solovyeva, Natalia (2021)
The article is devoted to problems of implementation in practice of the University of technology tutor support, which would allow modern students to quickly and painlessly build an individual trajectory of personal and professional development, and University – to implement the requirements of standard of the last generation. The article is based on observations of the included experiment on the implementation of tutor support, which was carried out in the framework of advanced training courses for teachers of PSNIU. During the experiment, conditions that are extremely important for ensuring the effectiveness of the implementation of tutor support technology were identified. Among them: the certainty (firmness) of the tutor's position in the implementation of a specific goal of tutor support; the importance of organizing spatial interaction during the tutorial; the formation of an adequate understanding of the content of the tutor's activity among the participants of the tutorial; recognition of the self-value of the tutor's activity.